MENINJAU KEMBALI GLASGOW COMA SCALE MASIHKAH RELEVAN - Arthur Hendrik Philips Mawuntu* (Neurona Majalah Kedokteran Neuro Sains, 2019)
COMA SCALE GCS IS THE MOST POPULAR QUANTITATIVE ASSESMENT OF CONSCIOUSNESS ITS POPULARITY IS GAINED BY THE SIMPLICITY OF THE ASSESSMENT MAKING THE SCALE EASY TO BE PERFORMED BY MEDICAL OFFICERS FROM VARIOUS BACKGROUND GLASGOW COMA SCALE WAS RAPIDLY ADOPTED WORLDWIDE SINCE ITS FIRST PUBLICATION IN 1974 THE WIDE ADOPTION OF THE SCALE HAS AFFECTED THE IMPROVEMENT OF HEAD INJURY MANAGEMENT AS WELL AS OTHER NEUROLOGICAL CONDITIONS